Smartphone Use and Academic Performance among Undergraduate Students: Analysis of Systematic Reviews - Sarumaha, Martiman Suaizisiwa (PT. Riset Press International, 2024)
The aim of this research is the systematic observations analyzed in this study explore the correlation between smartphone usage habits and learning outcomes among undergraduate students. The method used in this research is the Systematic Literature Review (SLR) Method. The SLR method is used to identify, review, research, and interpret all existing research on the phenomenon of the topic area of interest, with specific relevant research questions. By using the SLR method, systematic reviews and identification of journals can be carried out, in each process following predetermined steps or protocols. Data collection. Data Collection or data collection is the stage of collecting data for research. The results of the study are that by conducting a systematic review of the available literature, we can assess the relationship between smartphone use and academic performance among undergraduate students. The sources provided in the question do not directly address the relationship between smartphone use and academic achievement among undergraduate students. However, they provide information regarding various methodologies and methods used in studies of digital leadership and smartphone usage behavior. Therefore, although these sources do not provide direct evidence regarding the relationship between smartphone use and academic performance, they can provide insight into research methods and approaches that can be applied to investigate this issue. Additionally, studies on digital leadership highlight the importance of adaptability and effective communication in digital environments, which may be relevant to understanding the impact of smartphone use on academic performance. Based on the sources provided, both qualitative and quantitative studies are needed to comprehensively evaluate the relationship between smartphone use and academic achievement among undergraduate students.